Penentuan Karyawan Terbaik Dengan Sistem Pendukung Keputusan Metode Weighted Product - Purnamasari, Indah; Fajria, Maulfi (POLITEKNIK NEGERI JAKARTA, 2022)
Employees are one of the supporters in the progress, smoothness and success of a company. Quality employees are one of the company's assets that make the company grow rapidly. For this reason, employees with the best work ethic are entitled to promotions and incentives. In this study, a company has obstacles in selecting the best employees. So far, the determination of the best employees is still done manually, so that the determination of employees takes longer, is not transparent and ineffective. This can actually lead to new conflict problems among employees. Selection of the best employees aims to improve and evaluate employee performance. Therefore we need a Decision Support System to determine the best employees in a company so that it can be more transparent, more efficient, effective and acceptable to all parts of the company. The Weighted Product method is a more efficient method and the time required for calculations is easier and shorter in a Decision Support System. The selection of the Weighted Product Method is based on computational complexity which is not too difficult by obtaining a weight value for each attribute and a ranking process that will determine the best alternative. The results of this study are 0.14414 with criteria consisting of loyalty, productivity and quality of work, discipline, problem solving ability, cooperation, maintaining cleanliness, responsibility and work ability